2022
DOI: 10.1002/essoar.10512277.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bias correction of modelled urban temperatures with crowd-sourced weather data

Abstract: This a preprint and has not been peer reviewed. Data may be preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The simulations done in this research were performed using the WRF model v4.4 (https://github.com/wrf-model/ WRF.git). The related outputs presented in this research and codes used to plot them are available at Brousse et al (2024). The data used in the Supporting Information S1 for the study period selection and for model evaluation is publicly available.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations done in this research were performed using the WRF model v4.4 (https://github.com/wrf-model/ WRF.git). The related outputs presented in this research and codes used to plot them are available at Brousse et al (2024). The data used in the Supporting Information S1 for the study period selection and for model evaluation is publicly available.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The related outputs presented in this research and codes used to plot them are available at Brousse et al. (2024). The data used in the Supporting Information for the study period selection and for model evaluation is publicly available.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…To deal with higher degrees of uncertainty due to their inaccuracy 10,11 and human factors such as sub-optimal placement, multiple filtering algorithms have been developed to make this data more reliable [12][13][14][15] . PWS crowdsourced weather data are quickly becoming suitable and valuable for urban temperature studies and evaluation of models 16 . Pioneering studies have even suggested that they could be used to develop city-wide heat alarm systems 17 .…”
Section: Introductionmentioning
confidence: 99%